A comprehensive review of ethnopharmacology, phytochemistry, pharmacology, and pharmacokinetics of Schisandra chinensis (Turcz.) Baill. and Schisandra sphenanthera Rehd. et Wils. (10th February 2022) - Yang, Ke; Qiu, Jing; Huang, Zecheng; Yu, Ziwei; Wang, Wenjun; Hu, Huiling; You, Yu
Abstract: Ethnopharmacological relevance: Schisandra chinensis (called bei-wuweizi in Chinese, S. chinensis ) and Schisandra sphenanthera (called nan-wuweizi in Chinese, S. sphenanthera ) are two highly similar plants in the Magnoliaceae family. Their dried ripe fruits are commonly used as traditional Chinese medicine in the treatment of coughs, palpitation, spermatorrhea, and insomnia. They also are traditionally used as tonics in Russia, Japan, and Korea. Aim of the review: S. chinensis and S. sphenanthera are similar in appearance, traditional applications, ingredient compositions, and therapeutic effects. This review, therefore, aims to provide a systematic insight into the botanical background, ethnopharmacology, phytochemistry, pharmacology, pharmacokinetics, quality control, and toxicology of S. chinensis and S. sphenanthera, and to explore and present the similarities and differences between S. chinensis and S. sphenanthera . Materials and methods: A comprehensive literature search regarding S. chinensis and S. sphenanthera was collected by using electronic databases including PubMed, SciFinder, Science Direct, Web of Science, CNKI, and the online ethnobotanical database. Results: In the 2020 Edition of Chinese Pharmacopoeia (ChP), there were 100 prescriptions containing S. chinensis, while only 11 contained S. sphenanthera . Totally, 306 and 238 compounds have been isolated and identified from S. chinensis and S. sphenanthera, respectively. Among these compounds, lignans, triterpenoids, essential oils, phenolic acid, flavonoids, phytosterols are the major composition. Through investigation of pharmacological activities, S. chinensis and S. sphenanthera have similar therapeutic effects including hepatoprotection, neuroprotection, cardioprotection, anticancer, antioxidation, anti-inflammation, and hypoglycemic effect. Besides, S. chinensis turns out to have more effects including reproductive regulation and immunomodulatory, antimicrobial, antitussive and antiasthmatic, anti-fatigue, antiarthritic, and bone remodeling effects. Both S. chinensis and S. sphenanthera have inhibitory effects on CYP3A and P-gp, which can mediate metabolism or efflux of substrates, and therefore interact with many drugs. Conclusions: S. chinensis and S. sphenanthera have great similarities. Dibenzocyclooctadiene lignans are regarded to contribute to most of the bioactivities. Schisandrin A-C, schisandrol A-B, and schisantherin A, existing in both S. chinensis and S. sphenanthera but differing in the amount, are the main active components, which may contribute to the similarities and differences. Study corresponding to the traditional use is needed to reveal the deep connotation of the use of S. chinensis and S. sphenanthera as traditional Chinese medicine. In addition, a joint study of S. chinensis and S. sphenanthera can better show the difference between them, which can provide a reference for clinical application. It is worth mentioning that the inhibition of S. chinensis and S. sphenanthera on CYP3A and P-gp may lead to undesirable drug-drug interactions. Graphical abstract: Image 1